2018
DOI: 10.1155/2018/9156478
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Role of Circadian Rhythms in Bone Metabolism: A Promising Intervention Target?

Abstract: Numerous physiological processes of mammals, including bone metabolism, are regulated by the circadian clock system, which consists of a central regulator, the suprachiasmatic nucleus (SCN), and the peripheral oscillators of the BMAL1/CLOCK-PERs/CRYs system. Various bone turnover markers and bone metabolism-regulating hormones such as melatonin and parathyroid hormone (PTH) display diurnal rhythmicity. According to previous research, disruption of the circadian clock due to shift work, sleep restriction, or cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
46
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 138 publications
6
46
0
1
Order By: Relevance
“…The association between sleep quality and bone outcomes has been previously explained as an effect of sleep deprivation on circadian rhythms and thus the consequent changes that occur in bone metabolism [27]. Disruptions in the circadian clock have indeed been linked to abnormal bone metabolism and osteoporosis [28]. In our study, bone outcomes changed according to biological sex, and this can be linked to the fact that sleep quantity and quality varies with biological sex [3].…”
Section: Discussionsupporting
confidence: 52%
“…The association between sleep quality and bone outcomes has been previously explained as an effect of sleep deprivation on circadian rhythms and thus the consequent changes that occur in bone metabolism [27]. Disruptions in the circadian clock have indeed been linked to abnormal bone metabolism and osteoporosis [28]. In our study, bone outcomes changed according to biological sex, and this can be linked to the fact that sleep quantity and quality varies with biological sex [3].…”
Section: Discussionsupporting
confidence: 52%
“…It is a sensitive point in the network because it is the only gene in a mouse model where single gene knockout causes arrhythmias at the molecular and behavioral levels (Bunger et al, 2000). BMAL1 has been shown to be important in bone metabolism because the bone mass of BMAL1 KO mice is lower than that of wild-type mice (Song et al, 2018). Recently, researchers have discovered the role of circadian rhythm in the musculoskeletal system (Song et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…BMAL1 has been shown to be important in bone metabolism because the bone mass of BMAL1 KO mice is lower than that of wild-type mice (Song et al, 2018). Recently, researchers have discovered the role of circadian rhythm in the musculoskeletal system (Song et al, 2018). Recent studies have shown that chronic circadian rhythm disturbance interference is closely related to the development of osteoarthritis-like lesions of the knee joint in mouse, thus revealing circadian rhythm disturbance as a new risk factor for OA (Ranjan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Circadian clocks regulate various biochemical, cellular, and physiological processes with a periodicity of approximately 24 hours in order to maximize an organism's physiological efficiency . Studies have reported molecular links between circadian clocks and bone metabolism in mammals, including humans . For example, in humans, levels of the C‐terminal cross‐linked telopeptide of type I collagen (a bone resorption marker) and fibroblast growth factor 23 (a regulator of mineral metabolism) display a circadian rhythm .…”
Section: Discussionmentioning
confidence: 99%